2005
DOI: 10.2116/analsci.21.693
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Narrow-Band Tunable Picosecond Dye Laser and Its Application to Excited-State Lifetime Measurement of a Chlorinated Aromatic Hydrocarbon

Abstract: Supersonic jet/multiphoton ionization-mass spectrometry (SSJ/MPI-MS) is used in spectrometric analysis primarily because of its high selectivity. This approach provides wellresolved spectral features in the multiphoton ionization spectrum, and interference from other molecules, such as related analogues, can be minimized.In addition, information concerning molecular weight and chemical structure can be readily obtained from the mass spectrum. 1-3 Due to its high spectrometric selectivity, it can be used for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It has been reported that the maximal ionization efficiency is obtained when the pulsewidth of the laser is identical to or similar to the excited-state lifetime of the analyte molecule [3,4]. The lifetimes of a few chlorophenols have been reported elsewhere [5,6]. It is, however, well known that the toxicity equivalent (TEQ) is proportional to the concentration of chlorinated dibenzofuran, especially to that of pentachlorodibenzofuran; the correlation factor is reported to be much higher than 0.9, sometimes approaching 0.99 for a sample in the flue gas [7,8].…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that the maximal ionization efficiency is obtained when the pulsewidth of the laser is identical to or similar to the excited-state lifetime of the analyte molecule [3,4]. The lifetimes of a few chlorophenols have been reported elsewhere [5,6]. It is, however, well known that the toxicity equivalent (TEQ) is proportional to the concentration of chlorinated dibenzofuran, especially to that of pentachlorodibenzofuran; the correlation factor is reported to be much higher than 0.9, sometimes approaching 0.99 for a sample in the flue gas [7,8].…”
Section: Introductionmentioning
confidence: 94%
“…In this laser, only the initial spike of the laser emission induced by feed back of the beam (reflection at the surface of the dye cell) can be extracted by removing the pump energy remaining in the dye solution by generating a strong quenching beam that oscillates later than the impulse laser oscillation. 12,13 The picosecond pulse from the oscillator stage was then passed through an amplifier cell containing a coumarin 102 solution (7 × 10 -4 M). The pulse energy and the pulse width of the laser were measured by means of a joule meter (Molectron, J3-09) and a photodiode (Hamamatsu, C4258, rise time 50 ps) equipped with a 6-GHz digital oscilloscope (Tektronix, TDS6604B).…”
Section: Dye Lasermentioning
confidence: 99%
“…This laser was applied to measuring the singlet-excited state lifetime of a gas-phase aromatic hydrocarbon. 12 The tunable range can be extended from 320 nm to the entire visible region, when a Nd:YAG laser (266 nm) is used as a pump source.…”
Section: Introductionmentioning
confidence: 99%
“…[66][67][68] We recently reported on a tunable picosecond laser with a pulse width and a line width of 25 ps and 8.78 pm, respectivery. 69 This nearly Fourier-transform-limited pulse has the potential, not only for the efficient ionization of PCDD/Fs and their precursors, but also for the selective ionization of them, since the line width of this laser (∼0.01 nm) is about the same as the bandwidth of PCDD/Fs with the singlet-excitedstate lifetime of several picoseconds.…”
Section: ·1 the Use Of A Short Laser Pulsementioning
confidence: 99%